ANALISIS PENGGUNAAN MEDIA POWERPOINT SEBAGAI SUMBER BELAJAR PADA BIMBINGAN TEKNIS REKOGNISI PEMBELAJARAN LAMPAU (RPL) BAGI PERGURUAN TINGGI - Helsa Jumaipa WY; Rusdi Kurniawan; Dodi Mario Akbar; Zulfitria Zulfitria (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Recognition of Prior Learning (RPL) is a strategic higher education policy aimed at providing formal recognition of learning outcomes acquired through formal, non-formal, and informal education, and/or work experience. The complexity of RPL regulations and procedures, as stipulated in the Decree of the Director General of Higher Education Number 112/B/KPT/2025, requires effective and easily comprehensible policy dissemination strategies for higher education institutions. In practice, RPL technical guidance programs organized by the Directorate of Learning and Student Affairs are still predominantly reliant on PowerPoint as the primary medium for delivering instructional materials. This conceptual article aims to analyze the use of PowerPoint as a learning resource in RPL technical guidance for higher education institutions and to examine its reinforcement from the perspectives of educational technology, media and learning resource management, and andragogy. The study employs a conceptual analysis of RPL technical guidance practices conducted during the period 2023–2025. The findings indicate that PowerPoint is effective as a medium for presenting policy-related content; however, it needs to be supported by adult learning design and more systematic learning resource management in order to function optimally as a policy learning resource. This article recommends strengthening the role of PowerPoint through educational technology approaches and andragogical principles to enhance participants’ understanding and learning autonomy in RPL technical guidance programs. ABSTRAK Rekognisi Pembelajaran Lampau (RPL) merupakan kebijakan strategis pendidikan tinggi yang bertujuan memberikan pengakuan atas capaian pembelajaran yang diperoleh melalui pendidikan formal, nonformal, informal, dan/atau pengalaman kerja. Kompleksitas regulasi dan prosedur RPL, sebagaimana diatur dalam Keputusan Direktur Jenderal Pendidikan Tinggi Nomor 112/B/KPT/2025, menuntut strategi diseminasi kebijakan yang efektif dan mudah dipahami oleh perguruan tinggi. Dalam praktiknya, bimbingan teknis (bimtek) RPL yang diselenggarakan oleh Direktorat Pembelajaran dan Kemahasiswaan masih didominasi penggunaan media PowerPoint sebagai sarana utama penyampaian materi. Artikel konseptual ini bertujuan menganalisis penggunaan media PowerPoint sebagai sumber belajar dalam bimtek RPL bagi perguruan tinggi serta mengkaji penguatannya dari perspektif teknologi pendidikan, media dan pengelolaan sumber belajar, serta andragogi. Kajian dilakukan melalui analisis konseptual terhadap praktik bimtek RPL selama periode 2023–2025. Hasil kajian menunjukkan bahwa PowerPoint efektif sebagai media presentasi kebijakan, namun perlu didukung oleh desain pembelajaran orang dewasa dan pengelolaan sumber belajar yang lebih sistematis agar berfungsi optimal sebagai sumber belajar kebijakan. Artikel ini merekomendasikan penguatan peran PowerPoint melalui pendekatan teknologi pendidikan dan prinsip andragogi untuk meningkatkan pemahaman dan kemandirian belajar peserta bimtek RPL.